Discovering the effects of the implementation of the critical literacy practices in an efl classroom at a public institution in el Carmen de Viboral (2022)
The present qualitative study centres on the effects of the implementation of the critical literacy practices in tenth graders from a public institution in El Carmen de Viboral, Colombia. The study was accomplished through a survey, non-participant observations of the classes and two focus groups. The non-participant observations carried out during the gender stereotypes and gender ideology phenomenon classes. During the class discussions the students had the opportunity of speaking and interacting among them to understand their own context and realities, always oriented to a reflective process that allowed the students to have the power of taking action towards the change of their thinking. The findings that emerged from the instruments revealed that the critical literacy practices allowed the students to reformulate their conception or understanding of the social phenomena worked during the implementation, and also helped them reconstruct a new vision of their social realities based on the sense of power that this process left. At first, their English level of the students limited in some cases the students’ participation in class, but in the end the situation helped them to improve their language proficiency in different language skills. The students claimed that having classes framed under this approach favoured their learning process.